Tolerance of maize lines to the tembotrione herbicide (Research, Society and Development, 2022)
Maize inbred lines, due to their high level of homozygosity, have different behaviors from commercial hybrids in relation to herbicide sensitivity. Tembotrione, a post-emergence herbicide, widely used in the production of commercial corn hybrids, has been reported as causing phytotoxic effects. In this context, the objective of this work was to evaluate the phytotoxic potential of tembotrione, applied to six maize lines, assessing its effects over morphological and production aspects, with emphasis on photosynthesis. For this, an experiment was implemented in the municipality of Goianésia, in the brazilian Cerrado, during the dry season, using conventional sprinkler irrigation. The experimental design was randomized blocks, arranged in split plots with two factors: six maize inbred lines by four doses of tembotrione (0; 120; 240; and 480 mL ha-1). It was verified that there were no visual symptoms of toxicity in the genotype 43NG34381L with the application of 480 mL ha-1, even though it corresponded to twice that recommended in the label, being the inbred line more tolerant to the herbicide. The genotypes Z9999L, G55081L and 551CB, although sensitive to tembotrione at the label dose (240 mL ha-1), had moderate phytotoxicity at 7 days after application (DAA), without any symptoms at 14 and 21 DAA. The genotypes ZKQMR2357L and PGAG10051L were the most sensitive to the application of the herbicide tembotrione and maintained persistent symptoms of toxicity over time, even with the application of 240 mL ha-1. The yield of the ZKQMR2357L line was negatively affected by the toxicity caused by the herbicide.